The Nature and Structure of a Forensic Linguist’s Specialized Knowledge - V. O. Kuznetsov (Теория и практика судебной экспертизы, 2021)
The article addresses one of the current problems of forensic linguistics - the problem of a forensic linguist’s specialized knowledge. Basing on the study of the concept of “specialized knowledge” in legislation and the theory of forensic science and the practice of forensic linguistic analysis, the author demonstrates that a forensic linguist’s specialized knowledge is inhomogeneous in its nature. It is not limited to linguistic knowledge only but has a complex structure, which includes background knowledge, awareness of forensic science theory, and understanding of substantive and procedural law. It seems that at the present stage, such a structure of specialized knowledge of a forensic linguist most fully contributes to solving the tasks of forensic linguistics and implementing the principles of forensic expert activity regulated by Federal Law No. 73-FZ of 31.05.2001.